The Role of Arabic in Enriching the Indonesian Language Repertoire - Nurlis Nurlis; Lailatul khusniyah; Royyani rodloul Afifah (Edumaspul: Jurnal Pendidikan, 2024)
The arrival of Islam in Indonesia had a big influence on Indonesian society. This research tries to reveal the influence of Arabic on Indonesian which has long been consumed by Indonesian people in everyday language. This research uses a qualitative descriptive method with a loan word approach which results in many linguistic absorption phenomena occurring in the Indonesian language caused by Arabic, such as Arabic vocabulary whose spelling is relatively the same as the original having to experience vowel shortening, Arabic vocabulary undergoing changes. in pronunciation, Arabic vocabulary whose meaning is the same as the meaning intended in Arabic, and Arabic vocabulary whose meaning has changed from its original meaning. Arabic also influences loan words in Indonesia. This is because Arabic is a language that also contains Islamic religious and cultural concepts. Examples of influence can be seen from naming, use of expressions, use of literary terms and terms in state administration. There are similarities in Arabic vocabulary which is almost the same as Indonesian. Meanwhile, Arabic and Indonesian have a relationship with the majority of the Indonesian population, the majority of whom are Muslim, so that Arabic and Indonesian are the languages of preaching and the language of science.